Optimal investments for risk- and ambiguity-averse preferences: A duality approach - Alexander Schied (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
Ambiguity, also called Knightian or model uncertainty, is a key feature in financial modeling. A recent paper by Maccheroni et al. (2004) characterizes investor preferences under aversion against both risk and ambiguity. Their result shows that these preferences can be numerically represented in terms of convex risk measures. In this paper we study the corresponding problem of optimal investment over a given time horizon, using a duality approach and building upon the results by Kramkov and Schachermayer (1999, 2001). In many situations this seems to be the only feasible approach among the known techniques, as is illustrated by several examples.
Keywords: 330; Model uncertainty; ambiguity; convex risk measures; optimal investments; duality theory; Portfolio-Management; Duales Optimierungsproblem; Theorie